ChemInform Abstract: Regioselective Synthesis of N‐Heteroaromatic Trifluoromethoxy Compounds by Direct O—CF3 Bond Formation. Issue 33 (July 2016) - Liang, Apeng; Han, Shuaijun; Liu, Zhenwei; Wang, Liang; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract: This approach enables the unprecedented syntheses of a wide range of five‐or six‐membered N‐heteroaromatic trifluoromethoxy compounds containing one or two heteroatoms from most commonly used hydroxylated N‐heterocycles.